The Content And Essence Of Arabisms In The Epic "Sab'ai Sayyor". - Madaeva Mo'tabarkhan Amanullaevna (Peerian Journals Publishing, 2023)
Uzbek literature began to rise with Navoi's works. "Khamsa", written as a competition with Nizami and Khisrav Dehlavi, consists of five epics and contains about 50,000 verses. The epic "Saba'i Sayyor" in "Khamsa" uses a different molding style from other epics, and tells seven stories of seven strangers. The fourth and most amazing of the epics that make up Navoi's "Khamsa" is "Saba'i Sayyor". Alisher Navoi grew up reading literature in the Persian-Tajik language, and his interest in languages led him to study Arabic. His attention to the religion of Islam means that he memorized the Holy Qur'an, enriched his works with religious faith, read a lot of verses and hadiths, and mastered Arabic knowledge. Because Navoi embellished the work by using pure Arabic words in their place, and by using Arabic words together with Uzbek words, he enriched the Uzbek language with Arabic adaptations
Keywords: Uzbek language; Saba'i Sayyor